Turkey's Farmlands Policy: A Public Policy Process Analysis - Albayrak, Haydar (Fırat University, 2019)
In the study, after focusing what public policy analysis is and which methods are used for analysis, the agricultural policy is analyzed within the framework of Process Management Approach. In the analysis, firstly, the requirements that led to the emergence of policy recommendations, the policies adopted to meet the needs and the ways in which these were applied, and then the results were evaluated. At the end of the study, ıt was concluded that the process of determining public policy is not based on the needs in Turkey, the policy choice is based on the expectations of the day rather than the long-term rational targets, different policies are conflicting with each other on the same issues, the specified policies could not be implemented for a long time and therefore, the desired success could not be achieved.

Çalışmada kamu politikası analizinin ne olduğu, hangi yöntemler kullanılarak analiz yapıldığı üzerinde durulduktan sonra Süreç Yönetimi Yaklaşımı çerçevesinde Türkiye’nin tarım arazileri politikası analiz edilmektedir. Yapılan analizde ilk önce politika önerilerin ortaya çıkmasına neden olan ihtiyaçlara, ihtiyaçları gidermek için benimsenen politikalara ve bunların uygulanma şekilleri üzerinde durulmuş, ardından elde edilen sonuçlar değerlendirilmiştir. Çalışmanın sonunda Türkiye’deki kamu politika belirleme sürecinin ihtiyaç temelli olmadığı, politikaların uzun vadeli rasyonel hedeflere göre değil, günübirlik beklentilere göre belirlendiği, aynı konuda birbirleriyle çelişen farklı politikalar benimsendiği, belirlenen politikaların uzun süreli uygulanamadığı ve bu nedenle de beklenen başarının bir türlü elde edilemediği sonucuna ulaşılmıştır.
TÜRKİYE'NİN TARIM ARAZİLERİ POLİTİKASI: BİR KAMU POLİTİKASI SÜREÇ ANALİZİ